Above, Below, Before, and After Studies in Judaism and Christianity in Conversation with Martha Himmelfarb - Reed, Annette Yoshiko; Frankfurter, David; Boustan, Raanan; Boustan, Ra\anan (Mohr Siebeck, 2023)
Darüber, darunter, davor und danach. Studien zu Judentum und Christentum im Dialog mit Martha Himmelfarb.
PublicationDate: 20231206
Keywords: Second Temple Judaism -- Late Antiquity -- Second Baruch -- Pseudepigrapha -- Apocalypticism -- Textfunde vom Toten Meer -- ancient Mediterranean religion -- Messianism -- Neues Testament -- Kirchengeschichte -- Array